An abundance of Katherines - Green, John (United States : Dutton Books, 2006)
Having recenly dumped for the nineteenth time by a girl named Katherine, recent high school graduate and former child prodigy Colin sets off on a road trip with his best friend to try to find some new direction in life.
Keywords: Self perception- Fiction; Self perception- Fiction; Interpersonal relations-Fiction